COMPARISON OF 2D DEBRIS-FLOW SIMULATION MODELS WITH FIELD EVENTS - Rickenmann D.; Laigle D.; Mcardell B.W.; Hübl J. (My University, 2006)
Three two-dimensional (2D) debris-flow simulation models are applied to two large well-documented debris-flow events which caused major deposition of solid material on the fan. The models are based on a Voellmy fluid rheology reflecting turbulent-like and basal frictional stresses, a quadratic rheologic formulation including Bingham, collisional and turbulent stresses, and a Herschel–Bulkley rheology representing a viscoplastic fluid. The rheologic or friction parameters of the models are either assumed a priori or adjusted to best match field observations. All three models are capable of reasonably reproducing the depositional pattern on the alluvial fan after the models have been calibrated using historical data from the torrent. Accurate representation of the channel and fan topography is especially important to achieve a good replication of the observed deposition pattern.
Keywords: DEBRIS FLOW; FIELD OBSERVATION; FRICTION LAW; RHEOLOGIC PARAMETER; SIMULATION MODEL